Measurement of the B-d(0) oscillation frequency using kaons, leptons and jet charge - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; et al. (1996)
A measurement of the mass difference, Δmd, between the two physical Bd0 states has been obtained from the analysis of the impact parameter distribution of a lepton emitted at large transverse momentum (pt) relative to the jet axis and from the analysis of the flight distance distribution of secondary vertices tagged by either a high pt lepton or an identified kaon. In the opposite hemisphere of the event, the charge of the initial quark has been evaluated using a high pt lepton, a charged kaon or the mean jet charge. With 1.7 million hadronic Z0 decays recorded by DELPHI between 1991 and 1993, Δmd is found to be: Mathematical expression. © 1996 Springer-Verlag.